Effects of Melatonin Supplementation during Pregnancy on Reproductive Performance, Maternal-Placental-Fetal Redox Status, and Placental Mitochondrial Function in a Sow Model - Xie Peng; Xuelin Cai; Jian Li; Yingyan Huang; Hao Liu; Jiaqi He; Zhengfeng Fang; Bin Feng; Jiayong Tang; Yan Lin; Xuemei Jiang; Liang Hu; et al. (MDPI AG, 2021)
Melatonin (MT) is a bio-antioxidant that has been widely used to prevent pregnancy complications, such as pre-eclampsia and IUGR during gestation. This experiment evaluated the impacts of dietary MT supplementation during pregnancy on reproductive performance, maternal-placental-fetal redox status, placental inflammatory response, and mitochondrial function, and sought a possible underlying mechanism in the placenta. Sixteen fifth parity sows were divided into two groups and fed each day of the gestation period either a control diet or a diet that was the same but for 36 mg of MT. The results showed that dietary supplementation with MT increased placental weight, while the percentage of piglets born with weight < 900 g decreased. Meanwhile, serum and placental MT levels, maternal-placental-fetal redox status, and placental inflammatory response were increased by MT. In addition, dietary MT markedly increased the mRNA levels of nutrient transporters and antioxidant-related genes involved in the Nrf2/ARE pathway in the placenta. Furthermore, dietary MT significantly increased ATP and NAD+ levels, relative mtDNA content, and the protein expression of Sirt1 in the placenta. These results suggested that MT supplementation during gestation could improve maternal-placental-fetal redox status and reproductive performance by ameliorating placental antioxidant status, inflammatory response, and mitochondrial dysfunction.